2017
DOI: 10.1002/cbic.201700083
|View full text |Cite
|
Sign up to set email alerts
|

Sialylation Is Dispensable for Early Murine Embryonic Development in Vitro

Abstract: The negatively charged nonulose sialic acid (Sia) is essential for murine development in vivo. In order to elucidate the impact of sialylation on differentiation processes in the absence of maternal influences, we generated mouse embryonic stem cell (mESC) lines that lack CMP‐Sia synthetase (CMAS) and thereby the ability to activate Sia to CMP‐Sia. Loss of CMAS activity resulted in an asialo cell surface accompanied by an increase in glycoconjugates with terminal galactosyl and oligo‐LacNAc residues, as well a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 48 publications
1
38
0
Order By: Relevance
“…The Sia specificity of the lectin was again demonstrated by complete loss of SNA reactivity and an increase in PNA epitopes upon enzymatic removal of Sia by neuraminidase treatment prior to lectin incubation. The simultaneous lack of MAA and SNA reactivity and the presence of PNA binding sites in knockout embryos confirmed that loss of CMAS activity resulted in a complete lack of cell surface sialylation, referred to as an asialo phenotype, which is identical to the situation in Cmas -/-mESCs (9).…”
Section: Introductionmentioning
confidence: 61%
See 3 more Smart Citations
“…The Sia specificity of the lectin was again demonstrated by complete loss of SNA reactivity and an increase in PNA epitopes upon enzymatic removal of Sia by neuraminidase treatment prior to lectin incubation. The simultaneous lack of MAA and SNA reactivity and the presence of PNA binding sites in knockout embryos confirmed that loss of CMAS activity resulted in a complete lack of cell surface sialylation, referred to as an asialo phenotype, which is identical to the situation in Cmas -/-mESCs (9).…”
Section: Introductionmentioning
confidence: 61%
“…Depletion of CMAS leads to loss of sialoglycoconjugates in Cmas -/embryos and is embryonic lethal. Genetic inactivation of Cmas in mice was accomplished as described by excision of exon 4, which encodes residues essential for enzymatic activity (9). All genotypes of offspring from Cmas +/intercrosses were discovered in a Mendelian ratio until E8.5 (see Supplemental Figure 1; supplemental material available online with this article; https://doi.org/10.1172/ JCI99945DS1).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…xCGE‐LIF has been demonstrated as versatile HTS method for glycan analysis of complex biological samples to decipher even minor changes in N ‐glycan/oligosaccharide fingerprints . We here utilize xCGE‐LIF as an ideal method for high throughput monitoring of LNT and LNnT type oligomers from synthetic enzyme reactions.…”
Section: Resultsmentioning
confidence: 99%